Analysis of Fairness in Inheritance Distribution according to Badamai Customs among the Muslim Banjar Community in South Kalimantan - Syifa, Siti Nur; Akmal, Ahmad Wildan Rofrofil; Muzainah, Gusti; Ahmad, Ahmad; Ali, Ghifari Hirza Firhan (Universitas Muhammadiyah Surakarta, 2025)
The distribution of inheritance according to the Badamai custom is a form of customary inheritance law practised by the Muslim Banjar community in South Kalimantan. This custom results in an equal distribution pattern between male and female heirs. This study aims to analyze the value of justice within this equal distribution system using John Rawls’ Theory of Justice. Conducted as a field study with a sociological approach in South Kalimantan, the research draws on interviews with members of the Indigenous Muslim Banjar Community, community leaders, and supporting literature, including four journal articles. Viewed through Rawls’ theory, the Badamai inheritance system is considered fair because it aligns with two key principles. The first is the principle of equal liberty, which ensures that both men and women have the same fundamental right to inherit property. The second is the difference principle, which seeks to minimize inequality. By implementing equal distribution, the Badamai custom removes disparities in inheritance allocation, ensuring equal opportunities for all heirs. This study contributes to the development of Customary Inheritance Law and encourages local governments to support the establishment of the Badamai institution to help resolve inheritance-related disputes.